PENERAPAN STEGANOGRAFI GAMBAR BERWARNA PADA DELAPAN IMAGE COVER MENGGUNAKAN METODE LSB - Basri, Muh; Fadhlil Gushari, Muhammad (Jurnal Sintaks Logika, 2021)
Social interaction activities through devices connected to the internet, through computers, tablets and mobiles, have become activities that are often carried out. Advertising promotions, playing games, reading news, articles, or using social media, are some of the activities that can be done, and image activities are very important to support user interaction. By looking at the use of images on the internet, in this study an experiment will be conducted to see one of the unique things that can be done on the internet, namely hiding images in the images that have been provided, in the form of images that will be posted on social media accounts. Hiding The term can be termed as Steganography, By using LSB technology, the application that will be used can hide images into images.